CONFLICTING REMEMBRANCE: The Memory of the Macedonian 2001 in Context - Chupeska, Ana (Фондација Фридрих Еберт , Скопје (FES), 2023)
The Republic of North Macedonia’s post-2001 model of dealing with cultural diversity places the state among the more liberal ones and not among the states which tend to homogenize their culturally diverse population. In other words, North Macedonia’s institutions acknowledge the fact of societal multiculturality and it is reified and materialized in a concrete political system. In this text, I discuss the normative multiculturalism of a non-territorial kind in North Macedonia as based upon three pillars: group-specific rights and guaranteed representation; power-sharing and consociation; as well as concrete interventions in the symbolic order. All the three pillars in fact answer the question of why the normative solution proposed after the conflict functions in terms of the substantive democratic inclusiveness of minor communities within the political system, which indeed manifests via the norm that stimulates the need of everyday dialogue among the communities. Secondly, the pillars allow also for foundational power-sharing institutions without exhibiting any kind of territorial division, and with that the unity of the state is guaranteed (contrary to many examples of ethno-federalist power sharing arrangements). Thirdly, they allow a cultural autonomy for different cultural groups defined by the use of the unique mechanism of the reductive veto
THE MACEDONIAN MODEL OF NON-TERRITORIAL MULTICULTURAL ACCOMMODATION: NORMATIVE REFLECTIONS
/
Keywords: normative multiculturalism, non-territorial multicultural accommodation, North Macedonia, Ohrid Framework Agreement, political system